Effort Improvement Range of Motion (ROM), Overcoming Pain, and Repairing Balance in Cases Musculoskeletal Low Back Pain (LBP) with Hydrotherapy at Dr. M. Goenawan Partowidigdo Pulmonary Hospital - Chusnul Justati; Wiwit Azmi Lestari; Jamilatus Sholeha; Prima Dewi Kusumawati; Koesnadi (Journal of Community Engagement in Health, 2025)
Low back pain (LBP) is one problem frequent musculoskeletal​ happens in society. One of symptom main of LBP is decline range of motion (ROM) in the lumbar area. This decrease in ROM can cause limitations in activity daily patient, influence quality life they in a way overall. Fishbone diagram is used to identify various factor reason from problems faced.​ This diagram share internal causes​ categories like man, methods, machines, materials, measurements, and environment. The USG method (Urgency, Seriousness, Growth) is used to determine priority problem based on urgency, seriousness, and growth existing problems.​ SWOT analysis is used to evaluate existing strengths, weaknesses, opportunities and threats​ in context intervention hydrotherapy for LBP patients. Hydrotherapy proven effective in increase ROM and reduce pain in LBP patients at Dr. M. Goenawan Partowidigdo Pulmonary Hospital. With exists proper education and adequate facilities are expected​​ patient can overcome their LBP complaints and improve their quality life.